ANALISIS TINGKAT KEPUASAN NASABAH TERHADAP PRODUK LEMBAGA KEUANGAN ISLAM (Studi Kasus Lembaga Keuangan Islam Buana Kartika, Demak 2013) - Royyan Ramdhani Djayusman (University of Darussalam Gontor, 2013)
This study aims to analyze the level of customer satisfaction views of each product and service attributes analyzing customer satisfaction level on product IFI Buana Kartika Mranggen Demak . The product which is the object of research is the deposit and financing products IFIs Buana Kartika. This study used a 5 ( five ) dimensions of services quality namely reliability (reliability), responsiveness (responsiveness), guarantee (assurance), direct evidence (tangible) and empathy (empathy). In order to achieve the research used quantitative methods with a statistical analysis tool independent sample t - test by comparing the average performance level of IFI Buana Kartika with the average level of customer expectations . The results showed that significant value ratio and performance values for each variable, reliability ( 0.537 ) , responsiveness ( 0.249 ), Assurance ( 0,059 ), Tangible (0.240 ) and Emphaty ( 0,117 ) which is greater than the total value of the level significant 0.05 . That is, H0 stating “ there is no difference between the expected value and performance “ acceptable, meaning customers satisfied with every variable Reliability, Responsiveness, Assurance, Tangible and Emphaty in Islamic Financial Institutions Buana Kartika. In addition, if the value of the variable reliability sorted by the value 0.537 in the highest position which means a very high customer satisfaction rate on variable reliability. While the lowest position is variable with the assurance that the value of 0.059 indicates that the level of customer satisfaction at the lowest variable among other variables that has studied.